Eksplorasi Visual Efek Khusus - Asti Haningtyas, S.I.Kom, M.I.Kom, Asti Haningtyas, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2024)
This study reviews the extent to which special visual effects (VFX) will influence the film industry, with an emphasis on visual communication design, action scenes, and fantasy. Analysis of the latest Visual Effects (VFX) technologies, including hardware, software, and processing techniques, helps us understand advances in special effects production. This research explains how technology makes different film experiences with a focus on film case studies that focus on the influence of visual effects on character design and the construction of the film world. The research method is a literature review by understanding the history, technological developments, and impact of VFX in the film industry. The results of this study show that technology has an impact on film narrative and audience perception, ethical issues such as visual manipulation and unrealistic representation. Also, that of the use of visual effects in film production andthe possible misuse of technology, there are more ethical issues to be aware of in this industry. This research also details the anticipated technological developments such as augmented reality, virtual reality, andartificial intelligence, as well as their implications for visual communication design in films. The bottom line is that it is important to follow and use innovation with balanced training, skills, and ethical considerations in guiding the evolution of VFX in the film industry.